The quality of life of elderly Japanese residents of Chiang Mai: a case study of members of Japanese associations in Chiang Mai - Isao Yamaki,; Jarunee Dibyamandala,; Charin Mangkhang,; Chettapoom Wannapaisan, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study aims to investigate the quality of life of the elderly Japanese living in Chiang Mai. Chiang Mai is known as a city where many elderly foreigners live. Among them, the ratio of Japanese elderly is very high. Many previous studies have described the reasons for choosing Japanese aged people living in Chiang Mai mainly from the viewpoint of long-stayers. Whereas, the quality of life of the elderly Japanese who living in Chiang Mai did not reveal. The data were collected by using WHOQOL26. By survey method, conducted form 94 Japanese who joined the Japanese organization in Chiang Mai. As a result, in terms of “physical health” was in the range of 27-35, which was considered to be quite “good.” Followed by “psychological health” was in the range of 23-30, which was considered to be quite “good.” Despite, “social relationships” was in the range of 8-11, which was considered as “moderate.” In the other hand, “environment” was in the range of 30-40, which is considered to be quite “good.” Lastly, the overall was in the range of 96-130, which is considered to be “good.” Therefore, the survey confirmed that the quality of life of the elderly Japanese living in Chiang Mai was generally good.